2020
DOI: 10.1039/d0nj02895a
|View full text |Cite
|
Sign up to set email alerts
|

Bi-functional nature of nanoceria: pro-drug and drug-carrier potentiality towards receptor-mediated targeting of doxorubicin

Abstract: Nanoceria is considered to be one of the promising materials that modulate its pro-and anti-oxidant activity due to tuneable Ce3+/Ce4+ ratio under different physiological conditions. Present study explored the feasibility...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…13 The biological application of CeNPs either as potential diagnostic or therapeutic agents depends on their preserved physicochemical properties aer interacting with the cell culture media. [47][48][49] CeNPs coated with polymers such as polyethylene glycol has been reported to exhibit more cytotoxicity than non-coated CeNPs towards breast cancer cells. 49 Research reported in vivo study of erbium-doped CeNPs in treating acute liver injury by reducing the ROS products in the blood, 47 but the effect of these CeNPs cytotoxicity aer cellular uptake is unknown.…”
Section: Interaction Of Cenps With Human Cells and Their Impact On Cell Metabolic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…13 The biological application of CeNPs either as potential diagnostic or therapeutic agents depends on their preserved physicochemical properties aer interacting with the cell culture media. [47][48][49] CeNPs coated with polymers such as polyethylene glycol has been reported to exhibit more cytotoxicity than non-coated CeNPs towards breast cancer cells. 49 Research reported in vivo study of erbium-doped CeNPs in treating acute liver injury by reducing the ROS products in the blood, 47 but the effect of these CeNPs cytotoxicity aer cellular uptake is unknown.…”
Section: Interaction Of Cenps With Human Cells and Their Impact On Cell Metabolic Activitymentioning
confidence: 99%
“…[47][48][49] CeNPs coated with polymers such as polyethylene glycol has been reported to exhibit more cytotoxicity than non-coated CeNPs towards breast cancer cells. 49 Research reported in vivo study of erbium-doped CeNPs in treating acute liver injury by reducing the ROS products in the blood, 47 but the effect of these CeNPs cytotoxicity aer cellular uptake is unknown. Depending on the application, aiming for either more or less cytotoxicity towards the cells needs to be investigated by monitoring the CeNPs physicochemical properties aer entering the cellular environment.…”
Section: Interaction Of Cenps With Human Cells and Their Impact On Cell Metabolic Activitymentioning
confidence: 99%
“…Nevertheless, the most common among these methods remains chemotherapy [ 3 ]. Effective usage of common drugs in chemotherapy is often restricted due to their poor solubility, low biodistribution, systemic circulation as well as aggregation [ 4 ]. In addition, the non-specific delivery of these drugs is often associated with the use of higher doses to achieve the therapeutic dose, which can induce toxic effects on normal cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that their versatile characteristics based on high oxygen storage capacity (OSC) and low redox potential, ceria (CeO 2 ) nanoparticles (NPs) have garnered considerable interest in various fields for applications including solid oxide fuel cells, [1][2][3] UV shielding, 4 gas sensors, 5,6 biomedicine [7][8][9] and chemical mechanical planarization (CMP). [10][11][12][13] The unique properties of CeO 2 are attributed to their low vacancy defect formation energy, which causes oxygen vacancies on the surface of CeO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%